Síntese e caracterização do LiFePO4 dopado com Mn ou Co e seus compósitos com PDMcT/PAni para aplicação em dispositivos de armazenamento de energia - Fagundes, Wélique Silva (2020)
Energy storage systems are a key element in the development of sustainable energy technologies. In this context, this work aimed to synthesize cobalt or manganese doped lithium iron phosphate LiFePO4 samples at 5, 7.5 and 10% by the solvothermal method and associate it with poly(2,5dimercapto-1,3,4-thiadiazole) (PDMcT ) and polyaniline (PAni), forming binary and ternary composites to be tested as electrodes on supercapacitors. X-ray diffractograms (XRD) of LiFe1-xMnxPO4 samples synthesized at 200 oC, regardless of the percentage of dopant used, presented well-defined diffraction peaks, which were indexed to the orthorhombic structure. Among the cobalt or manganese doped LiFePO4 samples, LiFe0.9Mn0.1PO4 presented the lowest value of ΔEp (0.23 V) and Rct, (1139 Ω cm2). Therefore, binary and ternary composites were synthesized from the association between LiFe0.9Mn0.1PO4 and PDMcT in film form, using polyvinylidene fluoride (PVDF) as the binder agent, and the electrodeposition of PAni was performed over the electrode. The binary composites of PDMcT / PAni and LiFe0.9Mn0.1PO4 / PAni when subjected to 50 charge and discharge cycles at a current density of 1 mA cm-2, presented capacitance values of 147.31 and 93 F g-1, respectively. The ternary composite LiFe0.9Mn0.1PO4/PDMcT/PAni presented a specific capacitance of 108.7 F g-1 after 500 charge and discharge cycles with 83% retention capacitance in EC / DMC containing LiClO4 1 mol L-1, being selected for prototype assembly. The hybrid supercapacitor prototype (LiFe0.9Mn0.1PO4 / PDMcT / PAni | PAN / PVA 6% LiClO4 | Bi2O3 / Ppi) showed a specific capacitance value of 40.20 F g-1 after 150 charge and discharge cycles. In addition, the anodic charge values obtained from the prototype electrodes before and after the 150 charge and discharge cycles remained practically constant, indicating considerable electrochemical stability. Therefore, from the data obtained from the charge and discharge tests, it can be concluded that the ternary composite of LiFe0.9Mn0.1PO4/PDMcT/PAni is a promising material as supercapacitor electrode